Pengaruh pengetahuan dan keterpaan media massa terhadap sikap dan perilaku pencemaran lingkungan peserta didik SMA di Kota Makassar - Firdaus Daud; Muhammad Junda; Andi Citra Pratiwi (Seminar Nasional LP2M UNM, 2019)
This study aims to determine: 1) Knowledge, mass media exposure, attitudes, and environmental pollution control of high school students in Makassar City, 2) Effect of knowledge on environmental pollution attitudes, 3) Effect of mass media exposure to environmental pollution attitudes, 4) Influence knowledge of environmental pollution control, 5) Effect of information media vulnerability on environmental pollution control, 6) Indirect influence of knowledge on control through pollution, 7) Indirect influence of mass media on control through environmental pollution. The population of this study was all tenth grade students (X) majoring in Natural Sciences (IPA) of State High Schools in Makassar City. The sample was chosen by cluster random sampling, which was 177 people as respondents. The results showed: 1) Knowledge of environmental pollution of good qualifications, the comprehension of the mass media is of high tendency, the attitude of environmental pollution is a positive qualification, environmental pollution control qualifications are quite good, 2) Directly there is a significant influence of knowledge on the attitude of environmental pollution, 3) Directly there is a significant influence on the level of exposure of the mass media to the attitude of environmental pollution, 4) Directly there is a significant influence of knowledge on environmental pollution control, 5) Directly there is a significant effect on the level of exposure of the mass media to environmental pollution control, significant effect on environmental pollution control, 7) Indirectly the level of exposure to mass media through attitudes has a significant effect on environmental pollution control. Based on the results of the study, it is suggested to: environmental education teachers as well as others to try to increase knowledge, attitudes so as to form the ability to control environmental pollution for sustainable development, 2) Education experts should pay attention to the factors that are in direct contact with teacher needs in the field (bottom -up) in creating new approaches and methods in shaping attitudes and controlling environmental pollution.